Fishing : a Mr. and Mrs. Green adventure - Baker, Keith, 1953- (Green Light reader., 2012)
Mr. and Mrs. Green, a loving alligator couple, try their hand at fishing. Mrs. Green very upset because Mr. Green is catching all the fish, and her bucket is empty. She wonders if his secret is Mr. Green's lucky hat, his new fishing pole, or it has something to do with jelly beans.